254y-1=5

Create equivalent expressions in the equation that all have equal bases.

52(4y-1)=51

Since the bases are the same, then two expressions are only equal if the exponents are also equal.

2(4y-1)=1

Divide each term by 2 and simplify.

Divide each term in 2(4y-1)=1 by 2.

2(4y-1)2=12

Cancel the common factor of 2.

Cancel the common factor.

2(4y-1)2=12

Divide 4y-1 by 1.

4y-1=12

4y-1=12

4y-1=12

Move all terms not containing y to the right side of the equation.

Add 1 to both sides of the equation.

4y=12+1

Write 1 as a fraction with a common denominator.

4y=12+22

Combine the numerators over the common denominator.

4y=1+22

Add 1 and 2.

4y=32

4y=32

Divide each term by 4 and simplify.

Divide each term in 4y=32 by 4.

4y4=32⋅14

Cancel the common factor of 4.

Cancel the common factor.

4y4=32⋅14

Divide y by 1.

y=32⋅14

y=32⋅14

Multiply 32⋅14.

Multiply 32 and 14.

y=32⋅4

Multiply 2 by 4.

y=38

y=38

y=38

y=38

The result can be shown in multiple forms.

Exact Form:

y=38

Decimal Form:

y=0.375

Solve for y 25^(4y-1)=5